2013
DOI: 10.1073/pnas.1313473110
|View full text |Cite
|
Sign up to set email alerts
|

Naked mole-rat has increased translational fidelity compared with the mouse, as well as a unique 28S ribosomal RNA cleavage

Abstract: The naked mole-rat (Heterocephalus glaber) is a subterranean eusocial rodent with a markedly long lifespan and resistance to tumorigenesis. Multiple data implicate modulation of protein translation in longevity. Here we report that 28S ribosomal RNA (rRNA) of the naked mole-rat is processed into two smaller fragments of unequal size. The two breakpoints are located in the 28S rRNA divergent region 6 and excise a fragment of 263 nt. The excised fragment is unique to the naked mole-rat rRNA and does not show hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 46 publications
4
118
0
Order By: Relevance
“…This proposition is consistent with the predicted ancestor of NMR, DMR and guinea pig (Figure 1C). Following submission of our manuscript, a study by Azpurua and colleagues also found the unusual 28S processing in NMR tissues and proposed that the unique NMR 28S may result in improved protein synthesis fidelity and a more stable proteome (Azpurua et al, 2013). The NMR thus holds promise as a model organism to investigate the mechanism and function of ‘hidden breaks’ in ribosomal RNAs in a laboratory setting.…”
Section: Resultsmentioning
confidence: 89%
“…This proposition is consistent with the predicted ancestor of NMR, DMR and guinea pig (Figure 1C). Following submission of our manuscript, a study by Azpurua and colleagues also found the unusual 28S processing in NMR tissues and proposed that the unique NMR 28S may result in improved protein synthesis fidelity and a more stable proteome (Azpurua et al, 2013). The NMR thus holds promise as a model organism to investigate the mechanism and function of ‘hidden breaks’ in ribosomal RNAs in a laboratory setting.…”
Section: Resultsmentioning
confidence: 89%
“…The naked mole rat possesses a unique 28S rRNA species and the translational fidelity -the accuracy of the translation process at the ribosome -is much higher than in mouse cells (Azpurua et al, 2013). Using the same assay, we showed for the first time that translation accuracy is significantly decreased in CS cells, hence the quality of the translation is lower.…”
Section: Rna Polymerase I Might Play a Central Role In Cockayne Syndromementioning
confidence: 82%
“…For example, many studies examine different rodents, among which the lifespan can differ by ten-fold: two or three years for mouse or rat, and twenty or thirty years for blind mole-rat or naked mole-rat. Multiple alterations of genes or pathways contribute to their lifespan differences, including p16-INK4A or p53 in tumor suppression machinery [36][37][38], oxidative stress resistance [39,40], translation fidelity [41], autophagy [42,43], and insulin and mTOR signaling pathways [44,45], Ifnb1 and Mx1 in the interferon signaling pathway [46], and so on. In addition, other studies on longevity in large animals or flying long-lived animals also reveal a mixed pattern of strategies -interventions of both components in system capacity machinery and decision and regulatory circuitry.…”
Section: Lifespan Variations As a Reflection Of System Capacity Diffementioning
confidence: 99%